The effectiveness of integrating the Lumbung Hidup and Nutritional Rangers mobile applications in preventing stunting among underprivileged families in Kediri Regency - Prima Dewi Kusumawati; Reni Nurhidayah; Dhita Kurniasari (Healthcare in Low-resource Settings)
Stunting remains a significant public health issue in low and middle-income nations, including Indonesia. Globally, approximately 151 million children are affected by stunting. This study involved 22 children under five years old from economically disadvantaged families in Kediri Regency. Its aim was to assess the effectiveness of the Lumbung Hidup and Nutritional Rangers mobile applications in reducing stunting. Data analysis included both quantitative paired sample t-tests and qualitative thematic analysis methods. Results revealed significant improvements in children's nutritional status (p<0.05) across all Z-scores (weight-for-age, height-for-age, and weight-for-height), as well as five major qualitative themes. The significant improvements in Z-scores highlight the potential effectiveness of the integrated intervention in enhancing child nutrition. This comprehensive strategy could serve as a sustainable and holistic solution to address malnutrition and stunting, warranting broader implementation in similar settings.